The role of formal and non-formal education in the development of technological literacy: The case of aeromodelling club - Lemut Bajec, Melita (Revija za elementarno izobraževanje, 2023)
Education for technological literacy is a necessity of the 21st century if we want to educate individuals capable of planning, problem-solving, making informed decisions that will contribute to the proper use and advance of technology. Participation in free-time activities as a form of lifelong non-formal learning makes an important contribution to the child's overall development and serves to support formal education. The aim of the case study carried out among 20 participants was to explore their attitudes towards technical education; the challenges and tasks that it imposes on children, teachers and free-time technology–oriented activity instructors; and to evaluate the knowledge and skills it brings to children's lives.Keywords: technological literacy, technical education, primary school students, free-time activities, aeromodelling club